2016
DOI: 10.1039/c6tc02729f
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium phenanthroimidazole complexes for near infrared light-emitting electrochemical cells

Abstract: By adding different electron donor moieties to the ancillary ligand in ruthenium(ii) phenanthroimidazole complexes, we successfully designed near infrared light emitting complexes suitable for light emitting electrochemical cells (LECs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…Time‐dependent EQEs for all devices are shown in Figure c. The application of a bias corresponds to the rapid increase in the EQE because the carrier balance is improved through the formation of the doped layers. All complexes exhibit higher EL efficiencies than the reported iTMCs for saturated red LECs . The LECs based on RED1 and RED3 showed EQEs higher than 5 % owing to their tert ‐butyl substituents providing steric hindrance to avoid self‐quenching effects.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Time‐dependent EQEs for all devices are shown in Figure c. The application of a bias corresponds to the rapid increase in the EQE because the carrier balance is improved through the formation of the doped layers. All complexes exhibit higher EL efficiencies than the reported iTMCs for saturated red LECs . The LECs based on RED1 and RED3 showed EQEs higher than 5 % owing to their tert ‐butyl substituents providing steric hindrance to avoid self‐quenching effects.…”
Section: Resultsmentioning
confidence: 83%
“…Several studies on saturated red LECs, based on iTMCs, have been reported. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] However,m ost of these studies involve LECs that exhibit low or moderate device efficiencies (externalq uantum efficiency (EQE) < 3.3%); saturated red LECs that are moree fficienta re highlyd esired. In iridium iTMCs, the highest occupied molecular orbital (HOMO) is typicallyd istributed on the C^N ligands and metals, whereas the lowest unoccupiedm olecular orbital (LUMO) is locatedo nt he N^N ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bolink and co‐workers reported a radiance of 170 µW cm −2 peaked at 700 nm for a metal‐free cyanine‐based NIR‐LEC driven by a high‐frequency pulsed current. Shahroosvand and Bideh employed binuclear Ru complexes as the emitter and obtained a luminance of 742 cd m −2 at 690 nm, while Nazeeruddin and co‐workers reported NIR‐LECs based on mononuclear Ru complex that delivered a luminescence of 2395 cd m −2 at a peak wavelength 700 nm. Albeit promising, these studies suffer from that a high‐frequency operation depends on a converter circuit in mobile applications, that Ru is a rare and expensive compound, and that the measured lifetime of the Ru‐based NIR‐LEC was very limited at a mere 20 min.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is quite unusual considering the difficulties of synthesis of such complexes and the problems of solubility encountered with these polymetallic structures. This work is notably justified by the fact that LECs based on complexes comprising phenanthroimidazole ligands often lack the acceptable device stability for future applications, which could be improved by using di-nuclear complexes [109,110]. However, examination of LECs characteristics revealed that this challenge could not overcome with Ru-19 and Ru-20 , the time for LECs to reach half of the initial luminance being of only 539 and 1104 s for Ru-19 and Ru-20 -based devices, respectively (See Figure 7 and Table 4) [111].…”
Section: Metal Complexes Using Nir Emittersmentioning
confidence: 99%